2021
DOI: 10.3390/polym13091502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Modifier Types on the Physical–Mechanical Properties and Overall Migration of Post-Consumer Polypropylene/Clay Nanocomposites for Food Packaging

Abstract: The deterioration of the physical–mechanical properties and loss of the chemical safety of plastics after consumption are topics of concern for food packaging applications. Incorporating nanoclays is an alternative to improve the performance of recycled plastics. However, properties and overall migration from polymer/clay nanocomposites to food require to be evaluated case-by-case. This work aimed to investigate the effect of organic modifier types of clays on the structural, thermal and mechanical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…The unfilled PPW showed a T m of 164.6 °C, similar to the value reported in the literature for other PP wastes [ 12 ]. Two melting endothermic peaks (T m ) were observed for the PPW composites, one related to the melting of high density polyethylene (HDPE) at T m1 ~129 °C [ 38 , 55 ], and another one to the melting of PP at T m2 ~164 °C ( Figure 7 a). Other authors also reported the additional melting peak ascribed to HDPE during the heating process [ 27 , 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unfilled PPW showed a T m of 164.6 °C, similar to the value reported in the literature for other PP wastes [ 12 ]. Two melting endothermic peaks (T m ) were observed for the PPW composites, one related to the melting of high density polyethylene (HDPE) at T m1 ~129 °C [ 38 , 55 ], and another one to the melting of PP at T m2 ~164 °C ( Figure 7 a). Other authors also reported the additional melting peak ascribed to HDPE during the heating process [ 27 , 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Belviso et al [ 26 ] observed that recycled PP waste with a natural clay mineral and zeolite showed a decrease in the elongation of composites, due to the filler’s agglomeration leading to the weakening of interfacial interactions. Other researchers reported that the addition of n-clays improved the properties of recycled PP composites used for the treatment of textile dye waste water [ 37 ] or in food packaging [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Por estas propiedades hacen que el PP sea un polímero muy comercial comparado con otros polímeros de similares características; además, es de fácil procesamiento inicial y también en posconsumo haciéndolo ideal para múltiples aplicaciones en diferentes sectores de la industria (Velásquez et al, 2021). El PP se clasifica en homopolímeros y copolímeros, que generalmente son utilizados para fabricar envases que van a estar en contacto directo con alimentos, debido a que son químicamente inertes, termosellables y proporcionan una excelente barrera contra el agua (Hernández et al, 2001).…”
Section: Propiedades Del Polipropileno (Pp)unclassified
“…Polypropylene (PP), one of the most abundant thermoplastics, has been employed for fabricating polymer nanocomposites using a wide variety of nanofillers [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The hydrophobicity and chemical innerness of PP make uniform dispersion of nanoparticles challenging, for which various strategies have been reported.…”
Section: Introductionmentioning
confidence: 99%